2022
DOI: 10.1111/nph.18386
|View full text |Cite
|
Sign up to set email alerts
|

Floral and reproductive traits are an independent dimension within the plant economic spectrum of temperate central Europe

Abstract: Summary Major dimensions of plant ecological strategies have been widely studied bringing forward the concept of ‘economic spectra’ of plants. Sexual reproductive traits, ‘floral traits’, have been largely neglected in this context, despite their strong link to fitness. Here, we aimed at integrating floral traits into the dimensionality of plant form and function so far dominated by vegetative traits. We used principal component analyses and constructed trait networks to assess the correlation structure of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
16
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 92 publications
4
16
0
Order By: Relevance
“…Despite the enormous variability in plant reproductive structures, the first two and three axes captured over 50% and 70% of trait variation, respectively, and these axes encapsulated correlations among flower number and flower size, autonomous selfing and floral display, and style length and autonomous selfing. Although explained trait variation on the first two axes was less than previous studies of morphological and physiological traits (Carmona et al, 2021; Díaz et al, 2016), our results align with the two largest and most recent studies of plant life strategies that included reproductive‐, form‐ and size‐related traits (E‐Vojtkó et al, 2022; Salguero‐Gómez et al, 2016). The different plant reproductive axes that we identified were associated with different numbers of interacting partners and visitation rates of the distinct pollinator guilds.…”
Section: Discussionsupporting
confidence: 86%
“…Despite the enormous variability in plant reproductive structures, the first two and three axes captured over 50% and 70% of trait variation, respectively, and these axes encapsulated correlations among flower number and flower size, autonomous selfing and floral display, and style length and autonomous selfing. Although explained trait variation on the first two axes was less than previous studies of morphological and physiological traits (Carmona et al, 2021; Díaz et al, 2016), our results align with the two largest and most recent studies of plant life strategies that included reproductive‐, form‐ and size‐related traits (E‐Vojtkó et al, 2022; Salguero‐Gómez et al, 2016). The different plant reproductive axes that we identified were associated with different numbers of interacting partners and visitation rates of the distinct pollinator guilds.…”
Section: Discussionsupporting
confidence: 86%
“…For one species of forb, Linum lewisii , which flowered commonly over the course of the experiment, we also investigated (3) intraspecific plant trait variation within and across AMF treatments. Specifically, we hypothesized that (Hypothesis [H] 1) AMF enhance host plant vegetative biomass and floral traits; (H2) given that floral traits are strongly linked to fitness and play a distinctive role in the plant economic spectrum (E‐Vojtkó et al, 2022), AMF influence floral traits at least as strongly as vegetative biomass, though these effects would vary in magnitude depending on the AMF–plant pairing; and (H3) AMF treatments influence intraspecific trait variation.…”
mentioning
confidence: 99%
“…Recently, I was delighted to contribute to a paper published in New Phytologist by E‐Vojtkó et al . (2022) which showed that floral traits play a distinct role in the plant economics spectrum. In the context of plant–microbiome research, I liked the paper by Kiesewetter & Afkhami (2021) because it demonstrates the microbial contribution to plant ecology such as plant performance in a changing world.…”
Section: What Are Your Favourite New Phytologist Papers Of Recent Yea...mentioning
confidence: 99%